AVALIAÇÃO DO PESO E RENDIMENTO DE MIÚDOS COMESTÍVEIS E GORDURA ABDOMINAL DE FRANGOS DE CORTE ALIMENTADOS COM DDGS - RISSO, Natália Matos; DE SOUZA, Andréia Froés Galuci Oliveira; BRONSTRUP, Lamayson Gabriel Schirmann; MAAS, Adriano Rasia; DE MEDEIROS, Gabriel Dias; OVIEDO, Altair Rafael Vila (ANAIS DO ENIC, 2025)
-